A Bayesian chemical evolution model of the DustPedia galaxy M74 - Calura F.; Palla M.; Morselli L.; Spitoni E.; Casasola V.; Verma K.; Enia A.; Meneghetti M.; Bianchi S.; Pozzi F.; Gruppioni C. (My University, 2025)
We introduce a new, multizone chemical evolution model of the DustPedia galaxy M74, calibrated by means of Markov Chain Monte Carlo methods. We take into account the observed stellar and gas density profiles and use Bayesian analysis to constrain two fundamental parameters characterizing the gas accretion and star formation time-scale, i.e. the infall time-scale τ and the SF efficiency ν, respectively, as a function of galactocentric radius R. Our analysis supports an infall time-scale increasing with R and a star formation efficiency decreasing with R, thus supporting an 'Inside-Out' formation for M74. For both τ and ν, we find a weaker radial dependence than in the Milky Way. We also investigate the dust content of M74, comparing the observed dust density profile with the results of our chemical evolution models. Various prescriptions have been considered for two key parameters, i.e. the typical dust accretion time-scale τ0 and the mass of gas cleared out of dust by a supernova remnant, Mclear, regulating the dust growth and destruction rate, respectively. Two models with a different current balance between destruction and accretion, i.e. with an equilibrium and a dominion of accretion over destruction, can equally reproduce the observed dust profile of M74. This outlines the degeneracy between these parameters in shaping the interstellar dust content in galaxies. Our methods will be extended to more DustPedia galaxies to shed more light on the relative roles of dust production and destruction. © 2023 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.